First-principles calculation of hot carriers in black phosphorus - Villegas, Cesar E. P.; Rocha, Alexandre R. [UNESP] (IOP Publishing, 2020)
Black Phosphorus (BP), a layered semiconductor, has atracted enormous attention due to its singular anisotropic electronic, optical and thickness-dependent direct bandgap properties. As a consequence, BP has been envisioned as a promising material for several technological applications including photonics electronics and optolectronics. Nonetheless, most of the materials that integrate these devices undergo scattering and decay processes that are governed by quantum mechanical effects. From this point of view, the correct understanding and prediction of hot carriers dynamics in prospective materials as BP is crucial for its succesfull integration in future technology. In this work, based on ab initio calculations, we study the carrier relaxation rates in BP. Thus, the electron-electron and electron-phonon scattering contributions are investigated. Our results suggest that for the near-infrared and visible light spectrum [1.5 to 3.5 eV], the carriers in BP follow an ultrafast dynamics with relaxation times of the order of few to tens of femtoseconds while for the far-infrared range the relaxation times is of the order of hundreds of femtoseconds. Our reults are consistent with previous studies of pump-probe measurements on carrier dynamics.